Screening of Natural Molecules as Adjuvants to Topical Antibiotics to Treat Staphylococcus aureus from Diabetic Foot Ulcer Infections - Diana Oliveira; Anabela Borges; Maria J. Saavedra; Fernanda Borges; Manuel Simões (MDPI AG, 2022)
Diabetic foot ulcers (DFUs) are a common result of a complex secondary complication of diabetes mellitus. More than half of DFUs become infected due to frequent colonization with Staphylococcus aureus. The use of topical antibiotics is proposed, especially in combination with natural adjuvants, to minimize the negative impacts caused by generalized use of systemic antibiotics. In this study, 13 different phytochemicals-namely chalcone, juglone, cinnamic acid, trigonelline, Furvina-and four nitrovinylfuran derivatives-guaiazulene, α-bisabolol, farnesol and nerolidol-were selected to be tested as antibiotic enhancers. After minimum inhibitory and bactericidal concentration (MIC and MBC) determination of each molecule against different strains of S. aureus, including clinical isolates from diabetic foot wounds (CECT 976, Xu212, SA 1199B, RN4220, MJMC102, MJMC109, MJMC110 and MJMC111), their potentiation effects on the antibiotics fusidic acid, mupirocin, gentamicin, oxacillin and methicillin were evaluated through the disc diffusion method. Farnesol at sub-MIC was able to restore the activity of methicillin and oxacillin on the MJMC102 and MJMC111 strains, as well as two MRSA clinical isolates, and potentiated the effect of the remaining antibiotics. The results obtained demonstrate the great potential for the topical application of phytochemicals and derivatives as antibiotic resistance modifier agents to combat multidrug resistance in bacterial wound infections.